2019
DOI: 10.1097/bpo.0000000000001439
|View full text |Cite
|
Sign up to set email alerts
|

The Song Classification Is Reliable and Guides Prognosis and Treatment for Pediatric Lateral Condyle Fractures: An Independent Validation Study With Treatment Algorithm

Abstract: Background: Lateral condyle fractures account for 15% to 20% of pediatric elbow fractures. Among numerous proposed classification systems, the Song classification appears the most comprehensive. The utility of any classification system relies on its ability to be descriptive, reproducible, and to guide prognosis/treatment. We assessed the Song classification by applying it to 736 retrospectively treated patients. Methods: A total of 736 pediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…In our series, 22% of patients sustained major complications, in line with previous studies that reported complication rates ranging from 0 to 64%, after treatment of neglected LHC fractures [5][6][7][8][9][10][12][13][14][15][16][17][18]. This rate of complications is far higher than those following fresh fractures [1,[3][4][5]11,21]. We found significant associations between the modified CDS score for complications and the MEPS and DhiS at final follow-up, confirming that poorly treated and neglected LHC fractures can be harmful for long-term elbow function and quality of life, especially in athletic children [5].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our series, 22% of patients sustained major complications, in line with previous studies that reported complication rates ranging from 0 to 64%, after treatment of neglected LHC fractures [5][6][7][8][9][10][12][13][14][15][16][17][18]. This rate of complications is far higher than those following fresh fractures [1,[3][4][5]11,21]. We found significant associations between the modified CDS score for complications and the MEPS and DhiS at final follow-up, confirming that poorly treated and neglected LHC fractures can be harmful for long-term elbow function and quality of life, especially in athletic children [5].…”
Section: Discussionsupporting
confidence: 90%
“…Complications were classified according to the Clavien-Dindo-Sink (CDS) system; those with CDS > 2 were considered major complications [4,22]. Clinical and functional scores were recorded at baseline and at final follow-up.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment choice for LCF of the humerus depends on the fracture displacement and stability. A modified classification system has been proposed by Song et al [ 13 , 14 ] to clarify the ambiguity of Jakob type I fracture. Indication for surgery includes fractures with equally displaced medial and lateral gaps (Song type III) [ 15 ] and fractures with >2 mm displacement (Song type IV and V).…”
Section: Discussionmentioning
confidence: 99%
“…Justus et al reported a series of 172 patients with surgically treated LCHFs, where 18% (31) of the cases, including 13 Song stage 4 LCHFs and 4 Song stage 5 LCHFs, were treated with CRPP at the surgeons’ discretion [ 13 ]. However, Ramo et al could not replicate the success of CRPP in Song stage 5 LCHFs in their series [ 14 ]. We previously reported a series of 46 LCHFs displaced by > 2 mm at our institute, where CRPP was attempted with an approximate 75% success rate, even in Song stage 5 cases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%